2018
DOI: 10.1111/are.13589
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different procedures for fertilization and larvae production inHediste diversicolor(O.F. Müller, 1776) (Nereididae, Polychaeta)

Abstract: Different experimental trials were performed to clarify some aspects of the biology of the polychaete Hediste diversicolor (O.F. Müller, 1776) as a further step towards the development of appropriate breeding protocols for indoor farming systems. In particular, the trials were addressed to evaluate the effectiveness of two fertilization conditions (in vitro and “natural‐like”); induce gamete spawning by exposing mature individuals to thermal shock or to tissue homogenates; estimate the density effects on larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…The coloration of the adult worm can be picked out 1 or 2 months before the spawning seasons, which was considered the suitable time to collect the parental worms. Nesto et al (2018) kept the maturing worms in glass pipes (5 mm) placed in 50 ml tubes to prevent asynchronous spawning. We tested several glass pipettes with a diameter of around 5 mm placed in a plastic rectangle box to shelter the parental worms (Appendix Figure A3).…”
Section: Worm Stock Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The coloration of the adult worm can be picked out 1 or 2 months before the spawning seasons, which was considered the suitable time to collect the parental worms. Nesto et al (2018) kept the maturing worms in glass pipes (5 mm) placed in 50 ml tubes to prevent asynchronous spawning. We tested several glass pipettes with a diameter of around 5 mm placed in a plastic rectangle box to shelter the parental worms (Appendix Figure A3).…”
Section: Worm Stock Managementmentioning
confidence: 99%
“…Dales (1950) and Smith (1964) did not observe natural spawning under laboratory conditions, but Dales (1950) distinguished ripe females as reddish brown and the males as bright green which enabled the selection of broodstock for artificial fertilization. Nesto, Simonini, Prevedelli, and Da Ros (2018) used naturally spawned eggs in the laboratory to breed, but the natural spawned eggs had lower fertilization rates compared with in vitro fertilization. Ozoh and Jones (1990) found that fertilization of H. diversicolor was not affected in the ranges of temperature from 12 to 22°C, while the capacity adjustment of embryonic cleavage to increasing temperature deceased with increasing salinity.…”
mentioning
confidence: 99%
“…), extend of breeding season and/or cryopreservation of larvae to achieve larval supply all year round, develop appropriate breeding protocols (Nesto et al . ), optimize growth through control of nutrition with new diets (Santos et al . ), temperature and, if appropriate, photoperiod (Olive ), all contributing to improve the production of polychaetes.…”
Section: Polychaete's Potential For Aquaculturementioning
confidence: 99%
“…Polychaete aquaculture has been developed for several species but there are hurdles to develop this activity. Research that allowed knowledge to produce new native species can enhance the diversification of the bait produced, develop simple inexpensive systems for rearing juveniles (Garc ıa-Alonso et al 2013), extend of breeding season and/or cryopreservation of larvae to achieve larval supply all year round, develop appropriate breeding protocols (Nesto et al 2018), optimize growth through control of nutrition with new diets (Santos et al 2016), temperature and, if appropriate, photoperiod (Olive 1999), all contributing to improve the production of polychaetes.…”
Section: Other Suggestions Made Bymentioning
confidence: 99%
See 1 more Smart Citation